Pesan Nonverbal dalam Videoklip “Dunia Tipu-Tipu“ Yura Yunita - Alfreda, Evan; Lobodally, Altobeli (UNIVERSITAS KALBIS, 2025)
Nonverbal message is a message that packaged in a wordless form. The aim of this study was to determine the nonverbal messages in the video clip “Dunia Tipu-Tipu” Yura Yunita. This study was analyzed using the theory of Social Reality construction in the mass media.This research is using semiotic analysis methods were used to analyze nonverbal messages in the video clip “Dunia Tipu-Tipu”. The results of the study of nonverbal messages conveyed the meaning of a relationship without boundaries, shows the imagery as a construction of reality in the video clip. Reality is built as an image of a sincere nonverbal message. Deep closeness of mother and child who feel affection so that there is a fear of losing a mother and baby. A sense of dependence in the relationship. also a sense of mutual reinforcement and sharing in a friendly relationship.